Exploring situational awareness in diagnostic errors in primary care. Issue 1 (2nd September 2011) - Singh, Hardeep; Giardina, Traber Davis; Petersen, Laura A; Smith, Michael W; Paul, Lindsey Wilson; Dismukes, Key; Bhagwath, Gayathri; Thomas, Eric J
Abstract : Objective: Diagnostic errors in primary care are harmful but poorly studied. To facilitate the understanding of diagnostic errors in real-world primary care settings that use electronic health records (EHRs), this study explored the use of the situational awareness (SA) framework from aviation human factors research. Methods: A mixed-methods study was conducted involving reviews of EHR data followed by semi-structured interviews of selected providers from two institutions in the USA. The study population included 380 consecutive patients with colorectal and lung cancers diagnosed between February 2008 and January 2009. Using a pre-tested data collection instrument, trained physicians identified diagnostic errors, defined as lack of timely action on one or more established indications for diagnostic work-up for lung and colorectal cancers. Twenty-six providers involved in cases with and without errors were interviewed. Interviews probed for providers' lack of SA and how this may have influenced the diagnostic process. Results: Of 254 cases meeting inclusion criteria, errors were found in 30 of 92 (32.6%) lung cancer cases and 56 of 167 (33.5%) colorectal cancer cases. Analysis of interviews related to error cases revealed evidence of lack of one of four levels of SA applicable to primary care practice: information perception, information comprehension, forecasting future events, and choosing appropriate action based on the first three levels. In cases without error, application of the SA framework provided insight into processes involved in attention management. Conclusions: A framework of SA can help analyse and understand diagnostic errors in primary care settings that use EHRs.